Wkład artystycznej działalności rodziny Gimplów w światową kulturę: Внесок мистецької діяльності родини Ґімпелів у світову культуру - Мельник, Лідія (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2023)
This article deals with the challenge of the artistic family Gimpel family. Occasionally historical facts from activities of their representatives are already known and researched, however not connected. It is important to summarize the facts artistic activities of this dynasty, which was indeed important for world culture, at the same time demonstrate the tragic sides of their history. The individual cultural phenomena can only be understood comprehensively in an overall artistic and geopolitical context. For the first time activities of three generations of the Gimpel family being analyzed – one of the most significant artistic Jewish dynasties of Galicia during the late 19th century and first half of the 20th century. The life and career of Jacob Ber Gimpel (1840–1906), the patriarch of the dynasty and the founder of one of the first stationary Jewish theaters in Europe is traced in detail. Both his sons and successors Emil (Samuel Mendel, 1867–1942) and Adolf (Aaron, 1875–1942) and grandchildren, including Maurycy (1897–1942), Emil’s son, a lawyer by education, who continued to lead the theater with his wife, actress Malvina Yoles (1900–1942), as well as the sons of Adolf made a huge contribution to world music culture. Karol Gimpel (1901–1942), a pianist, was a reputated figure in the musical life of interwar Warsaw. Jacob Gimpel (1906–1989) became a world-famous pianist and Oscar winner, and Bronislaw Gimpel (1911–1979) a world-famous violinist. This article analyzes reasons for the success and decline of the Gimpel Jewish Theater, describes the tragic fate of their family members, who fell victim to the Holocaust and the international fame of the two youngest descendants.